2013
DOI: 10.1371/journal.pone.0059489
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones and Electrocardiographic Parameters: Findings from the Third National Health and Nutrition Examination Survey

Abstract: IntroductionAltered thyroid status exerts a major effect on the heart. Individuals with hypo- or hyperthyroidism showed various changes in electrocardiograms. However, little is known about how variations in thyroid hormone levels within the normal range affect electrical activities of the heart in the general population.Methods and ResultsWe conducted a cross-sectional analysis of 5,990 men and women from the Third National Health and Nutrition Examination Survey. Serum total T4 was measured by immunoassay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…Thyroid hormone exerts both electrophysiological and ionotropic effects on the heart and may increase the risk of developing atherosclerosis [2]. Patients with hyperthyroidism can develop atrial arrhythmias such as sinus tachycardia, atrial flutter, atrial fibrillation, both prolonged and shortened QT interval [2]. It is also linked with angina, rarely myocardial infarction and sudden death [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormone exerts both electrophysiological and ionotropic effects on the heart and may increase the risk of developing atherosclerosis [2]. Patients with hyperthyroidism can develop atrial arrhythmias such as sinus tachycardia, atrial flutter, atrial fibrillation, both prolonged and shortened QT interval [2]. It is also linked with angina, rarely myocardial infarction and sudden death [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 12% of the US population will develop a thyroid condition during their lifetime, and an estimated 20 million Americans have already some form of thyroid disease [1] . Besides, some of the most prominent and common symptoms of thyroid disease are those that result from the effects of thyroid hormone on the heart and cardiovascular system [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] . Both hyperthyroidism and hypothyroidism produce changes in cardiac contractility, myocardial oxygen consumption, cardiac output, blood pressure, and systemic vascular resistance [12] , [13] , [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that these changes might be related with increased risk of arrhythmias [6]. A recent paper also reported prolonged QT intervals in the NHANES (National Health and Nutrition Examination Survey) population with low normal thyroid hormone levels [7]. Kweon et al studied the effects of levothyroxine supplementation on QT interval and QT dispersion in hypothyroid patients and found that levothyroxine therapy significantly decreased the QT intervals and QT dispersion [8].…”
Section: Discussionmentioning
confidence: 99%